2007
DOI: 10.1007/s11095-007-9509-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mucosal Damage and Recovery in the Gastrointestinal Tract of Rats by a Penetration Enhancer

Abstract: Absorption barrier recovery could be measured using a poorly absorbed marker. Functional recovery showed a good correlation with morphological recovery. The local effects of SDS were found to be temporary and reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 61 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…Pretreatment with C 10 for 15 min (followed by removal) did not increase FD4 absorption when the flux marker was administered 15 min later, in marked contrast to the significant absorption promotion seen when both agents were administered together or when FD4 was administered within 10 min (Wang X, PhD Thesis, NUI Dublin 2009). While another promoter, SDS, increased phenol red absorption in rat intestine, its effects took longer than C 10 to dissipate [118]. In another rat perfusion study, co-administration of either SDS, EDTA, or C 10 with cefoxitin increased absorption of the antibiotic [113]; upon removal of the promoter, cefoxitin plasma levels continued to increase with SDS and EDTA, but not in the case of C 10 .…”
Section: [12] Intestinal Absorption Promotersmentioning
confidence: 98%
“…Pretreatment with C 10 for 15 min (followed by removal) did not increase FD4 absorption when the flux marker was administered 15 min later, in marked contrast to the significant absorption promotion seen when both agents were administered together or when FD4 was administered within 10 min (Wang X, PhD Thesis, NUI Dublin 2009). While another promoter, SDS, increased phenol red absorption in rat intestine, its effects took longer than C 10 to dissipate [118]. In another rat perfusion study, co-administration of either SDS, EDTA, or C 10 with cefoxitin increased absorption of the antibiotic [113]; upon removal of the promoter, cefoxitin plasma levels continued to increase with SDS and EDTA, but not in the case of C 10 .…”
Section: [12] Intestinal Absorption Promotersmentioning
confidence: 98%
“…alcohol, food (spices and fatty meals) and drug molecules (e.g., non-steroidal anti-inflammatory drugs, laxatives and chenodeoxycholate, a bile salt used to dissolve gall stones). [42][43][44] Every 3 days the small intestinal epithelia is entirely renewed, and each day, 10 11 epithelial cells are shed. 45,46 There is a high rate of cellular turnover and the intestine has a high capacity to replace cells, due to migrating stem cells from the intestinal crypt (Fig 1).…”
Section: Normal Repair Mechanismmentioning
confidence: 99%
“…49 Stage 2 is restitution or migration, where adjacent healthy epithelia begin crawling using lamellipodia in order to patch exposed areas between cells. 43 A number of cofactors including polyamines and trefoil peptides are also involved. Stage 3 is restoration of the barrier involving repair and closure of paracellular spaces.…”
Section: Normal Repair Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well known that the instilled rat intestinal mucosa is restituted within 45 min in response to exposure to surfactants, including SDS [47] and C10 [48], investigations of Caco-2 monolayer recovery have not gone much beyond noting the restoration of basal levels of transepithelial electrical resistance (TEER) in fresh medium, a process that can take up to 24 h (e.g., [49]). However, HCA revealed that, when Caco-2 cells were exposed to 8.5mM C10 for 60 min, nuclear intensity, intracellular calcium, nuclear area, plasma membrane potential, mitochondrial membrane potential, and cell number were all increased [33].…”
Section: Hca: Cytotoxicity Of Polymers and Permeation Enhancersmentioning
confidence: 99%